Agile productivity unleashed : proven approaches for achieving real productivity gains in any organisation - Cooke, Jamie Lynn (IT Governance Publication, 2010)
In today's challenging economic climate, organizations faced with limited budgets and frozen staffing levels need proven, common-sense approaches to maximize their productivity. Agile approaches are business practices with a proven track record for helping organizations achieve greater efficiency, higher-quality outputs and increased customer satisfaction. They enable organizations to avoid the trappings of extensive up-front planning and up-front budget commitments by encouraging staff to regularly produce high-value business outputs; and by basing ongoing financial and resource commitments on the delivered outcomes. This focus on responsive planning based on tangible results is why Agile approaches have been successfully used in selected industries for over two decades. This book introduces every industry sector to the Agile approaches that have dramatically improved the IT, product development and manufacturing sectors over the past two decades. The book clearly explains how the key principles of Agile approaches can be used to significantly increase productivity, quality and customer satisfaction in every business activity at your organization. Written in non-technical language specifically for business professionals, this book is an essential tool for anyone whose job it is to deliver high-quality results on time and on budget.